Studi Kasus: Urolithiasis Pada Kucing Mezza di Surabaya - Astuti, Mery; Hermawan, Intan Permatasari (JURNAL KAJIAN VETERINER, 2023)
The most common disease of the lower urinary tract in cats is FLUTD. FLUTD (Feline lower urinary tract disease) is asyndrome that affects the reproductive tract, bladder or urethra. A cat named Mezza weighing 3.85 kg, 2.5 years old,was brought to the K and P Surabaya clinic on May 18 2022 with complaints of not being able to urinate for two days,not wanting to eat, drinking little, physically weak when brought . The results of the palpation examination of the catMezza showed that the urinary bladder was large, round in shape, and the cat was in pain when palpating, the resultsof a microscope examination of the urine sample found the presence of oxalate crystals. On physical examination thecat's body temperature was 38.5 °C, its physical condition looked active, slightly dehydrated but did not appear pale.Based on the anamnesis, physical examination and supporting examinations, it can be concluded that the Mezza cat isinfected with Urolithiasis and the prognosis is fausta. Ringer's lactate solution was chosen as fluid therapy. The injectiontherapy given is enrofloxacin and dexamethasone. Oral drugs given include fibumin, cystaid and Nutriplus gel. After thefourth day of therapy, the case cat whose urine was initially red had changed to a normal yellow color, and it wasobserved that until the fifth day, Mezza's cat's urination began to flow smoothly.